Potential Utilization of Lamtoro Leaves (Leucaena leucocephala) as Natural Coagulants - Riva Ismawati; Rina Rahayu; Rizqa Puspitarini (Universitas Tidar, 2023)
Water is a vital element for human beings. However, there are still limited clean water services in Indonesia. Raw water treatment is needed to ensure the availability of clean water. One of the methods is by using the coagulation process. The coagulant functions to speed up the coagulation process. Although effective in water treatment, chemical coagulants have some disadvantages. Therefore, it is necessary to develop natural coagulants to overcome the weakness of chemical ones. Natural ingredients can be used as coagulants if they have many macromolecules. Lamtoro leaves are one of the natural materials that are only used to feed the animal. This research aims to examine the potential of lamtoro leaf as a natural coagulant in terms of its content. The research is conducted by testing lamtoro leaf powder using Fourier Transform Infrared Spectroscopy and proximate test. Infrared spectra of lamtoro leaves show the presence of absorption peaks for specific groups of carbohydrate and protein compounds. The proximate test results show that lamtoro leaves contain 24.7% protein and 53.71% carbohydrates. The high protein and carbohydrate contents in lamtoro leaves enable them to be used as a natural coagulant.